A systematic review of the burden of hypertension, access to services and patient views of hypertension in humanitarian crisis settings. Issue 11 (9th November 2020) - Keasley, James; Oyebode, Oyinlola; Shantikumar, Saran; Proto, William; McGranahan, Majel; Sabouni, Amar; Kidy, Farah
Abstract : Introduction: Globally, a record number of people are affected by humanitarian crises caused by conflict and natural disasters. Many such populations live in settings where epidemiological transition is underway. Following the United Nations high level meeting on non-communicable diseases, the global commitment to Universal Health Coverage and needs expressed by humanitarian agencies, there is increasing effort to develop guidelines for the management of hypertension in humanitarian settings. The objective was to investigate the prevalence and incidence of hypertension in populations directly affected by humanitarian crises; the cascade of care in these populations and patient knowledge of and attitude to hypertension. Methods: A literature search was carried out in five databases. Grey literature was searched. The population of interest was adult, non-pregnant, civilians living in any country who were directly exposed to a crisis since 1999. Eligibility assessment, data extraction and quality appraisal were carried out in duplicate. Results: Sixty-one studies were included in the narrative synthesis. They reported on a range of crises including the wars in Syria and Iraq, the Great East Japan Earthquake, Hurricane Katrina and Palestinian refugees. There were few studies from Africa or Asia (excluding Japan). The studies predominantly assessed prevalence of hypertension. This varied with geography and age of the population. Access to care, patient understanding and patient views on hypertension were poorly examined. Most of the studies had a high risk of bias due to methods used in the diagnosis of hypertension and in the selection of study populations. Conclusion: Hypertension is seen in a range of humanitarian settings and the burden can be considerable. Further studies are needed to accurately estimate prevalence of hypertension in crisis-affected populations throughout the world. An appreciation of patient knowledge and understanding of hypertension as well as the cascade of care would be invaluable in informing service provision.